THE INFLUENCE OF GREEN MANURE CROP, MINERAL FERTILIZERS AND HUMATES ON WEED INFESTATION OF CROP AREA AND YIELDING ABILITY IN CHICORY - O. M. Vjutnova; E. A. Evseeva (Овощи России, 2018)
The study was carried out in 2011-2013 with the use of local variety of root chicory ‘Yaroslavskyi’. It was shown that application of green manure crops such as pea-oat mixes and fertilizers significantly raised the number of leaves from 11, as in control to 20.6, as it was observed in variant after ploughing pea-oat mixes supplemented with N60P60K120 + В + humate. The well-developed leaf apparatus and improved photosynthetic potential in plant have been obtained up to 1.54 million m2 days/ha. Green manure crop precursors had a positive impact on weed infestation in crop area. The least number of weeds was observed with application of pea-oat mixes as precursors, 15.8 pcs /m2. The analysis of fertilizer action showed that the highest yield of chicory roots, 38.4 ton/ha had been observed with supplementation of fertilizers in rates N60P60K120 + В, and plant treatment with humates, where the addition was in ratio to fertilized ground of 13.5 ton/ha or 54,2%. According to three-year-results the following variant oat+pea+ N60P60K120 + В + humates had been recommended to be submitted for experimental and production trial testing. With application of recommended variant the more vigorous development of leaf apparatus was observed. The cultivation of chicory on pea-oat mixes supplemented with mineral fertilizers and ‘Humistar’ gave the improvement in yield for all years of testing and was on the average 40,8 ton/ha, or 129,5% to control variant. The conditional net profit was 129.1 thousand rubles/ha; true cost was 2.8 thousand rubles/ha; profitability was 56.3%.